Perspectives on Population in AP® Human Geography. Issue 3 (3rd May 2016) - Lu, Max; Keller, Kenneth
ABSTRACT: A study of human geography begins with the human population. In fact, demographic topics frequently relate to other units in the AP Human Geography course. The three main concepts elaborated upon in this article are (1) the demographic transition model, (2) Malthusian theory and its critics, and (3) pronatalist and antinatalist policies that might be implemented by governments in attempts to increase or decrease national populations. The article also suggests appropriate resources and classroom practices that may be used to teach these topics.